Effects of non-invasive vagus nerve stimulation on clinical symptoms and molecular biomarkers in Parkinson’s disease - Mondal, Banashree; Choudhury, Supriyo; Banerjee, Rebecca; Roy, Akash; Chatterjee, Koustav; Basu, Purba; Singh, Ravi; Halder, Saptak; Shubham, Shantanu; Baker, Stuart N.; Baker, Mark R.; Kumar, Hrishikesh (Frontiers in Aging Neuroscience, 2024)
Non-invasive vagus nerve stimulation (nVNS) is an established neurostimulation therapy used in the treatment of epilepsy, migraine and cluster headache. In this randomized, double-blind, sham-controlled trial we explored the role of nVNS in the treatment of gait and other motor symptoms in Parkinson’s disease (PD) patients. In a subgroup of patients, we measured selected neurotrophins, inflammatory markers and markers of oxidative stress in serum. Thirty-three PD patients with freezing of gait (FOG) were randomized to either active nVNS or sham nVNS. After baseline assessments, patients were instructed to deliver six 2 min stimulations (12 min/day) of the active nVNS/sham nVNS device for 1 month at home. Patients were then re-assessed. After a one-month washout period, they were allocated to the alternate treatment arm and the same process was followed. Significant improvements in key gait parameters (speed, stance time and step length) were observed with active nVNS. While serum tumor necrosis factor- α decreased, glutathione and brain-derived neurotrophic factor levels increased significantly (p < 0.05) after active nVNS treatment. Here we present the first evidence of the efficacy and safety of nVNS in the treatment of gait in PD patients, and propose that nVNS can be used as an adjunctive therapy in the management of PD patients, especially those suffering from FOG. Clinical trial registration: identifier ISRCTN14797144.